Expression of Echinococcus granulosus recombinant EgAg5-38 sub-unit and P-29 antigens and evaluation of their diagnostic potential for cystic echinococcosis in buffaloes - TIGGA, MARY NISHA; RIALCH, AJAYTA; ARUN, A; SAMANTA, S; KAUR, NAVNEET; BAURI, R K; GANAIE, Z A; AFTAB, ANDLEEB; RAINA, O K (The Indian Journal of Animal Sciences, 2017)
There are no routine, reliable diagnostic methods for detection of Echinococcus granulosus infection, the causative agent of cystic echinococcosis in human and domestic animals. Two recombinant proteins EgAg5-38 sub-unit and P-29 of E. granulosus were expressed in prokaryotic expression vectors. The diagnostic potential of these two recombinant proteins was evaluated in the detection of cystic echinococcosis in buffaloes in IgG-ELISA. The EgAg5-38 sub-unit and P-29 recombinant protein reacted fairly with the hydatid infected buffaloes with EgAg5-38 sub-unit showing sensitivity and specificity of 67.9 and 78.8%, respectively. However, the recombinant P-29 protein showed a higher sensitivity of 82.1% but a low specificity of 43.9% in the detection of hydatid infection in buffaloes. Cross-reactivity of these recombinant antigens in buffaloes naturally infected with several gastrointestinal trematodes and Sarcocystis was studied. The results showed that both these antigens cross-reacted with most of these parasites of buffaloes. Present study is the first report on the evaluation of diagnostic potential of E. granulosus recombinant EgAg5-38 sub-unit and P-29 antigens in buffaloes.